A dark winter - Llewellyn, Claire (Cambridge : Cambridge University Press, Cambridge, 2017)
Welcome to Karasjok! Find out what it is like to live in Northern Norway where it is dark for much of the winter. Non-fiction texts in Turquoise Band use maps, charts and diagrams to present information. Learners are encouraged to navigate information displayed in glossaries and indexes. Contains full teaching support including learning outcomes, curriculum links and follow-up activities.
Keywords: Juvenile - works; Norway - Karasjok